1988
DOI: 10.1007/bf00058839
|View full text |Cite
|
Sign up to set email alerts
|

Chromosomal polymorphism and extra bristles of Drosophila melanogaster: joint variation under selection in isofemale lines

Abstract: Selection for increased numbers of dorsocentral and scutellar bristles produced an increase of In(3R)C heterozygotes in isofemale lines of D. melanogaster. The influence of polygenic selection in the maintenance of the chromosomal polymorphism is discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
6
0

Year Published

1991
1991
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…The regions analyzed were exon, intron, 5′ UTR, 3′ UTR, upstream, downstream intergenic, and splice. There are some chromosomal inversions segregating in the populations we studied, and they are known to contribute to adaptation (Wright and Dobzhansky 1946; García‐Vázquez and Sánchez‐Refusta 1988; Kapun et al. 2014).…”
Section: Methodsmentioning
confidence: 99%
“…The regions analyzed were exon, intron, 5′ UTR, 3′ UTR, upstream, downstream intergenic, and splice. There are some chromosomal inversions segregating in the populations we studied, and they are known to contribute to adaptation (Wright and Dobzhansky 1946; García‐Vázquez and Sánchez‐Refusta 1988; Kapun et al. 2014).…”
Section: Methodsmentioning
confidence: 99%
“…There are some chromosomal inversions segregating in the populations we studied and they are known to contribute to adaptation (Wright and Dobzhansky 1946; García-Vázquez and Sánchez-Refusta 1988; Kapun et al 2014). We tested whether the relationship between clinal and seasonal variation is stronger inside within inversions.…”
Section: Methodsmentioning
confidence: 99%
“…The regions analyzed were exon, intron, 5’ UTR, 3’ UTR, upstream, downstream intergenic and splice. There are some chromosomal inversions segregating in the populations we studied, and they are known to contribute to adaptation (Wright and Dobzhansky 1946; García-Vázquez and Sánchez-Refusta 1988; Kapun et al 2014). We annotated SNPs surrounding (2Mb) common inversion breakpoints and added inversion status as a covariate in the linear model (Corbett-Detig and Hartl 2012).…”
Section: Methodsmentioning
confidence: 99%
“…Many studies have reported associations between chromosomal inversions and phenotypic traits in Drosophila (e.g., Battaglia & Smith, 1961;De Jong & Bochdanovits, 2003;Dobzhansky & Pavlovsky, 1961;Dobzhansky & Spassky, 1962;Durmaz, Benson, Kapun, Schmidt, & Flatt, 2018;Etges, 1989;García-Vázquez & Sánchez-Refusta, 1988;Hoffmann & Rieseberg, 2008;Hoffmann & Weeks, 2007;Hoffmann et al, 2004;Kapun, Schmidt, Durmaz, Schmidt, & Flatt, 2016;Krimbas & Powell, 1992;Lemeunier & Aulard, 1992;Sperlich & Pfriem, 1986). However, only few studies have isolated and phenotyped a large number of chromosomal lines to examine the effects of inverted vs. noninverted chromosomes on fitness components (i.e., life history traits), the major phenotypic targets of selection (Durmaz et al, 2018;Kapun, Schmidt et al, 2016).…”
mentioning
confidence: 99%
“…Unfortunately, despite the experimental tractability of the D. melanogaster model, almost nothing is known about the phenotypic effects of other inversions in this species (Lemeunier & Aulard, 1992). One exception is the finding that the frequency of In(3R)C is correlated with bristle number and that artificial selection for increased bristle number increases the frequency of this inversion (García-Vázquez & Sánchez-Refusta, 1988;García-Vázquez, Sanchez-Refusta, & Rubio, 1989;Izquierdo, García-Vázquez, & Villar, 1991). Moreover, a series of studies showed that In(2L)t heterokaryotypes exhibit overdominance with regard to fecundity and fertility in Japanese populations (Watanabe, 1969;Watanabe & Watanabe, 1973;Watanabe, Watanabe, & Oshima, 1976).…”
mentioning
confidence: 99%